Rescuing Diskmags: Towards Scholarly [Re]Digitisation of an Early Born-Digital Heritage - Roeder, Torsten (magazén, 2022)
Disk magazines are a special type of periodical that was published on floppy disk mainly in the 1980s and 1990s. Created by home computer enthusiasts for the community, disk magazines are potentially valuable as a historical resource to study the experiences of programmers, users and gamers in the early stage of microcomputing. The material preserved by fan communities could be a starting point to derive scientifically reliable resources. Creating a digital scholarly edition from the material needs not only to consider the original encoding and hardware standards, but also include the necessary role of emulation and hardware preservation.